Goldilock Returns - Ernst, Lisa Campbell 1832-1898.; Sir, 1820-1914 (New York Simon & Schuster, 2000)
Fifty years after Goldilocks first met the three bears, she returns to fix up their cottage and soothe her guilty conscience.
Issued also with marginal illustrations.
Keywords: Bears - Fiction; Humorous stories